Pengaruh Absensi Dan Efektivitas Kerja Terhadap Kinerja Pegawai Dengan Gaya Kepemimpinan Sebagai Variabel Moderasi Pada DISPORAPAR Kota Metro - Sekar Ayuni; Suwarto; Nina Lelawati (Universitas Muhammadiyah Metro, 2025)
The HR Performance Assessment aims to ensure the objectivity of civil servant development which is based on an achievement system and career system. Assessments are carried out based on performance planning at the individual level and unit or organization level, taking into account targets, achievements, results and benefits achieved, as well as employee behavior. In this case, the researcher intends to look at HR assessment in terms of employee attendance and work effectiveness with leadership style as an element that can strengthen the influence of these two things on employee performance. This research aims to find out whether absenteeism has an effect on employee performance, to find out whether work effectiveness has an effect on performance, to find out whether absenteeism has an effect on employee performance which is moderated by leadership style and to find out whether work effectiveness has an effect on employee performance which is moderated. by leadership style. The sample for this research was all employees at DISPORAPAR Metro City, totaling 48 people. Data collection used questionnaires and literature studies, and data analysis used validity tests, reliability tests, normality tests, linearity tests, homogeneity tests, moderated regression analysis, T tests, and coefficient of determination tests (R2) using the program (SPSS). The research results show that there is an influence on employee performance through absenteeism and work effectiveness and leadership style can moderate the influence of absenteeism and work effectiveness on employee performance.